Small-size 2.5 MeV electron accelerator with local radiation shielding - Gavrish, Yu.N.; Klinov, A.P.; Krestianinov, A.S.; Nikolaev, V.M.; Fomin, L.P.; Linkenbach, H.A.; Geus, G.; Knospel, W. (Вопросы атомной науки и техники, 2001)
A novel design of a 2.5 MeV small-size linear electron accelerator with local radiation shielding is presented in the paper. The accelerator is intended for the use in mobile introscopic facilities. The main design approaches, weight / dimensions and results of factory tests are given.